New record of the monotypic shrimp genus Procletes (Decapoda:Pandalidae) from the West coast of India (UNED Research Journal, 2019)
Introduction: Significant work has been done on the diversity and distribution of pandalid shrimps in Indian waters but reports did not include the presence of this species. Objective: To list the marine shrimps of Gujarat. Methods: Samples were collected from trawl catch. Results: Procletes levicarina is reported for first time from the coastal area of Gujarat, including a detailed morphological description and photographs. This species is previously reported from the east coast of India. Conclusion: Procletes levicarina occurs in the west coast of India.
Keywords: pandalid; shrimp; Procletes; Spence Bate; new record; Gujarat